Sequencing and Analysis of Strobilanthes cusia (Nees) Kuntze Chloroplast Genome Revealed the Rare Simultaneous Contraction and Expansion of the Inverted Repeat Region in Angiosperm - Chen, Haimei; Shao, Junjie; Zhang, Hui; Jiang, Mei; Huang, Linfang; Zhang, Zhao; Yang, Dan; He, Molly; Ronaghi, Mostafa; Luo, Xi; Sun, Botao; Wu, Wuwei; et al. (Frontiers in Plant Science, 2018)
Ban-Lan-Gen, the root tissues derived from several morphologically indistinguishable plant species, have been used widely in traditional Chinese medicines for numerous years. Identification of reliable markers to distinguish various source plant species is critical for the effective and safe use of products containing Ban-Lan-Gen. Here, we analyzed and characterized the complete chloroplast (cp) genome sequence of Strobilanthes cusia (Nees) Kuntze to identify high-resolution markers for the species determination of Southern Ban-Lan-Gen. Total DNA was extracted and subjected to next-generation sequencing. The cp genome was then assembled, and the gaps were filled using PCR amplification and Sanger sequencing. Genome annotation was conducted using CpGAVAS web server. The genome was 144,133 bp in length, presenting a typical quadripartite structure of large (LSC; 91,666 bp) and small (SSC; 17,328 bp) single-copy regions separated by a pair of inverted repeats (IRs; 17,811 bp). The genome encodes 113 unique genes, including 79 protein-coding, 30 transfer RNA, and 4 ribosomal RNA genes. A total of 20 tandem, 2 forward, and 6 palindromic repeats were detected in the genome. A phylogenetic analysis based on 65 protein-coding genes showed that S. cusia was closely related to Andrographis paniculata and Ruellia breedlovei, which belong to the same family Acanthaceae. One interesting feature is that the IR regions apparently undergo simultaneous contraction and expansion, resulting in the presence of single copies of rps19, rpl2, rpl23, and ycf2 in the LSC region and the duplication of psbA and trnH genes in the IRs. This study provides the first complete cp genome in the genus Strobilanthes, containing critical information for the classification of various Strobilanthes species in the future. This study also provides the foundation for precisely determining the plant sources of Southern Ban-Lan-Gen.